Changes in Specialists' Perspectives on Cancer Genetic Testing, Prophylactic Surgery and Insurance Discrimination: Then and Now. Issue 2 (13th July 2013) - Matloff, Ellen T.; Bonadies, Danielle C.; Moyer, Anne; Brierley, Karina L.
Abstract: We surveyed cancer genetics specialists in 1998 to learn what they would do if at 50 % risk to carry a BRCA or Lynch syndrome mutation. We chose to repeat our study 14 years later, to examine how perspectives have changed with the extensive data now available. In July 2012 we surveyed the National Society of Genetic Counselors (NSGC) Cancer Special Interest Group via an internet based survey. We found statistically significant increases in the percentage of specialists who: would undergo BRCA testing ( p = 0.0006), opt for prophylactic bilateral mastectomy ( p =0.0001), opt for prophylactic removal of their uterus and ovaries for Lynch syndrome ( p =0.0057 and P = 0.0090, respectively), and bill testing to insurance ( p >0.0001). There were also statistically significant decreases in the percentage of participants who would have their colon removed for Lynch syndrome ( p = 0.0002) and use an alias when pursuing testing ( p > 0.0001). Over the past 14 years there has been a major change in perspective amongst cancer genetic specialists regarding genetic testing, prophylactic surgery and insurance discrimination.